Some ability training and children's mental development training process issues - Steponaitienė, L. (Psichologija, 1968)
The issue of ability development in the educational process is very relevant, though not sufficiently developed in literature. Knowledge accumulation and application in learning was considered for one subject, or even in the context of a single topic. Our research included 4th-9th grades and the entire roster of subjects (biology, physics, and chemistry).This article summarizes the experimental investigation on ability development and details of its relationship with the student's mental development. On the basis of data obtained it can be said that abilities are closely linked with knowledge, they have a positive effect on the strength of knowledge, destroy formality, and expanding them. Along with the development of the abilities, the student's abilities in using analysis, synthesis, and clarifying understanding are increasing. Practical abilities become intellectual. If abilities are trained during interdisciplinary lessons, students will be able to look at things from different angles and have a broader perspective.Research showed that abilities have a positive impact teaching students to use their minds well. The article explains this phenomenon.
Keywords: abilities; ability development; mental development